PROMOSI, POIN LOYALITAS DAN KUALITAS PELAYANAN SEBAGAI PEMBENTUK KEPUTUSAN PEMBELIAN MELALUI APLIKASI BURGER KING - Florencia Putri Soetanto; Saino Saino (Program Studi Akuntansi, 2022)
This study aims to assess the influence of promotion, loyalty points, and service quality on the purchasing decisions of Burger King application products. This form of research uses hypothesis testing methodology and is quantitative. A total sample of 96 eligible people have purchased Burger King Sidoarjo through the application and the number of samples used at the beginning of the study. This sampling uses a method or questionnaire that is distributed through a questionnaire. The results of the data analysis are as follows: (1) Promotions have a significant effect on purchasing decisions made through the Burger King application; (2) Loyalty points have a significant effect on purchasing decisions made through the Burger King app; and (3) The quality of service has a significant effect on purchasing decisions made through the Burger King app. (4) Promotions, loyalty points, and quality of service affect burger king app purchasing decisions.